An information-processing framework for understanding reading disability - Spear, L.C.; Sternberg, R.J. (Handbook of Cognitive, Social, and Neuropsychological Aspects of Learning Disabilities, 2014)
Several years ago, when the senior author of this chapter taught in a resource room for learning-disabled children, she made a disturbing discovery. This discovery involved the reading-disabled youngsters, who comprised the majority of the children in the program. All these youngsters entered the program with poor decoding skills, but once exposed to the intensive phonic program used in the resource room, they generally learned to decode individual words with alacrity; that is, they could grasp phonic rules, memorize sounds for various letters and letter combinations, and apply the rules and sounds when reading individual words. The disturbing thing, particularly to someone who had had excessive faith in the curative powers of a phonic approach to teaching reading, was that the children continued to be poor readers. Now, however, their difficulties involved higher level aspects of reading. Their oral reading was discontinuous, effortful, and sometimes painfully slow; their reading comprehension was frequently poor; and the older children lacked the study strategies so important for success in content area subjects such as social studies and science. © 2014, Stephen J. Ceci. All rights reserved.
Keywords: dept.sed

Deaf writers' application of american sign language knowledge to english - Wolbers, Kimberly A; Bowers, Lisa M; Dostal, Hannah M; Graham, Shannon C (International Journal of Bilingual Education and Bilingualism, 2014)
Language transfer theory elucidates how first language (L1) knowledge and grammatical features are applied in second language (L2) writing. Deaf and hard of hearing (d/hh) students who use or are developing American Sign Language (ASL) as their L1 may demonstrate the use of ASL linguistic features in their writing of English. In this study, we investigated the extent to which 29 d/hh students in Grades 6-8 (mean age=13.2) with diverse ASL exposure incorporated ASL features in their English writing. We also investigated the impact of one year of Strategic and Interactive Writing Instruction (SIWI) to increase students' metalinguistic knowledge and linguistic competence, and subsequently reduce ASL features in writing. Results indicate that ASL transfer is found in the writings of students with varied L1 experiences, and that SIWI can lead to significant reductions of ASL features in writing. The findings suggest that bilingual literacy programs where there is an emphasis on implicit language competence and metalinguistic knowledge can support d/hh students in the development of written English.
Keywords: ASL; bilingual education; deaf; dept.sed; language transfer; writing

Prosody growth and reading comprehension : a longitudinal study from 2nd through the end of 3rd grade - Lopes, João; Silva, Maria Madalena; Moniz, Antonio Vargas; Spear-Swerling, Louise; Zibulsky, Jamie (Revista De Psicodidactica, 2014)
Prosody is an important but not fully understood component of reading. In this longitudinal study with a sample of 98. Portuguese elementary school children, a multilevel growth model with four repeated measures over time showed steady progress in participants’ reading prosody from the middle of 2nd to the end of 3rd grade. However, children’s growth in this area varied across time points. Results also showed that individual differences in prosody’s scores at baseline affect the performance of most but not of all students. Simple linear regressions showed that the prosody dimension “phrasing/expression” significantly predicted reading comprehension at all time points. Partial correlation analysis showed that when reading rate was accounted for, the unique contribution of prosody to reading comprehension was marginal, except at the third measurement © UPV/EHU.
Keywords: Prosody; Reading comprehension; Reading prosody; dept.sed

Making time for literacy: teacher knowledge and time allocation in instructional planning - Spear-Swerling, Louise; Zibulsky, Jamie (Reading and Writing, 2014)
This study examined how K-5 general and special educators (N = 102) would choose to allocate time in a 2-h language arts block if they could do so as they wished, and how these choices related to their knowledge base for reading instruction. Preferences for time allocation were assessed through an open grid on which participants listed descriptions of planned instructional activities and amount of time for each activity; teacher knowledge was assessed via a multiple-choice measure involving questions about assessment and instruction in the five components of reading. Results showed that many teachers planned little or no time for areas such as assessment, vocabulary, phonemic awareness, and spelling; also, relatively little time was devoted to basic writing skills and virtually none to writing processes such as planning or revision. There were few significant differences between general and special educators in time allocation on the grid, although there were more differences by grade level (e.g., grids for Grades K-1 vs. Grades 4-5). Teacher knowledge did predict teachers' time allocation plans, particularly for teachers with relatively high knowledge of phonemic awareness and phonics. Overall, however, many teachers chose to allocate time in ways inconsistent with scientific recommendations, in writing as well as in reading. The study highlights the importance of research-based, targeted teacher professional development in literacy, as well as the need for schools to provide comprehensive, research-based core reading and writing curricula to educators, with attention to fidelity of implementation.
Keywords: Literacy; Reading; Reading instruction; Teacher beliefs; Teacher knowledge; Writing instruction; dept.sed; peer-reviewed